Fast-charging low-temperature graphite composite material as well as preparation method and application thereof

By growing carbon nanotubes in porous graphite and depositing lithium sulfonate on their shells to form a graphite composite material with a core-shell structure, the diffusion coefficient deviation of the existing fast-charging graphite materials under low temperature conditions is solved, and the fast charging of the material and its low-temperature performance are significantly improved.

CN119601634APending Publication Date: 2025-03-11广东宏璟新能源科技有限公司

Patent Information

Application Number
CN202411789813.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The diffusion coefficient deviation of existing fast charging graphite materials under low temperature conditions leads to limited improvement in their low temperature performance.

Method used

Carbon nanotubes are grown in porous graphite, and lithium sulfonate is deposited on their shells by spray drying to form a graphite composite material with a core-shell structure.

Benefits of technology

It improves the electronic conductivity and lithium ion embedding rate of the material, significantly improving its fast charging and low-temperature performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601634A_ABST
    Figure CN119601634A_ABST
Patent Text Reader

Abstract

The invention discloses a fast-charging low-temperature graphite composite material, a preparation method and application thereof, the composite material is of a core-shell structure, the core is porous graphite and a carbon nanotube doped with the porous graphite, and the shell is composed of a lithium supplement agent and a lithium sulfonate complex of the lithium supplement agent. The preparation method comprises the following steps: soaking porous graphite in a conductive polymer solution, adding a catalyst, a cross-linking agent and an oxidizing agent, carrying out oxidative polymerization and carbonization to obtain catalyst-doped porous graphite, and introducing carbon source gas through a vapor deposition method to obtain carbon nanotube-doped porous graphite; and adding the obtained material into a lithium sulfonate solution, adding a lithium supplement agent, uniformly mixing, and carrying out spray drying to obtain the graphite composite material. According to the obtained material, the electronic conductivity of the material is improved by using the carbon nanotubes grown on the inner core, and the lithium sulfonate coated on the outer shell has relatively strong solvation capability, so that the transmission rate of lithium ions is improved, and the rate capability is improved; meanwhile, the lithium supplement agent releases lithium ions in the charging and discharging process, the first efficiency is improved, and the low-temperature and fast-charging performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium ion battery material preparation, and specifically relates to a fast-charging low-temperature graphite composite material, a preparation method and application thereof. Background Art

[0002] As the market's requirements for fast charging and low-temperature performance of lithium-ion batteries increase, the negative electrode materials used are required to have excellent fast charging performance and good low-temperature performance. The main factors affecting the fast charging and low-temperature performance of graphite negative electrode materials are: particle size, carbon coating amount, different coating methods and types of coating agents. The fast-charging graphite on the market currently mainly coats 2-3% of soft carbon or hard carbon on the surface of small-sized graphite particles to improve the fast charging and low-temperature performance of the material. However, there are defects such as deviation in the electronic conductivity of the coating layer material and slow ion transfer rate, which have limited improvement in the fast charging and low-temperature performance of the material. Although some researchers have improved the electronic or ionic conductivity of the material by coating carbon nanotube conductive agents or lithium salt compounds in the shell, the coating layer has poor uniformity and poor compatibility with the lithium salt compound in the coating layer and the electrolyte, which has limited improvement in the fast charging and low-temperature performance of the material. For example, patent application number CN201910220710.8 discloses a porous lithium salt aerogel-coated graphite composite material and a preparation method thereof. The composite material has a core-shell structure, with the core being graphite and the shell being a porous lithium aluminate / lithium silicate / lithium titanate ternary complex, which improves the material's initial efficiency and rate performance. However, since the lithium salt coating layer material has a porous structure and poor electronic conductivity, and the three lithium salt compounds are all inorganic lithium salts and have general compatibility with electrolyte solvents, the diffusion coefficient of lithium ions deviates at low temperatures, and the improvement in the low-temperature performance of the material is limited. Summary of the invention

[0003] In order to further improve the fast charging and low temperature performance of existing fast charging graphite, the present invention obtains a graphite composite material by growing carbon nanotubes in porous graphite and depositing lithium sulfonate on its outer shell by spray drying. At the same time, a preparation method of a fast charging and low temperature graphite composite material is provided.

[0004] A fast-charging, low-temperature graphite composite material, characterized in that the composite material presents a core-shell structure, the core is porous graphite and doped carbon nanotubes, and the shell is composed of a lithium supplement and a lithium sulfonate complex; calculated based on the mass ratio of the composite material being 100%, the shell accounts for 2-8wt%.

[0005] A fast-charging low-temperature graphite composite material, characterized in that the shell is composed of 5-20wt% lithium supplement, 40-70wt% lithium sulfonate, and the rest is lithium binder.

[0006] A method for preparing a fast-charging low-temperature graphite composite material, characterized in that it comprises the following steps:

[0007] Step S1:

[0008] According to the mass ratio of porous graphite: catalyst: organic polymer: oxidant: anhydride cross-linking agent = 100: 1-5: 10-30: 5-20: 1-5, the organic polymer is dissolved in an organic solvent to prepare a 1-10wt% solution, then the catalyst, anhydride cross-linking agent, and porous graphite are added and dispersed evenly, then the oxidant is added dropwise and dispersed evenly, and the mixture is reacted at a temperature of 0-15°C for 1-6h, filtered, and the obtained filter residue is carbonized at 1000-1400°C for 2-12h to obtain catalyst-doped porous graphite;

[0009] Step S2:

[0010] The catalyst-doped porous graphite is transferred to a tube furnace, and then the temperature is raised to 800-1000° C. by a vapor deposition method, and a carbon source gas is introduced at a flow rate of 100-500 SCCM for 30-300 minutes to obtain carbon nanotube-doped porous graphite;

[0011] Step S3:

[0012] According to the mass ratio of lithium sulfonate: carbon nanotube-doped porous graphite: lithium supplement: organic solvent = 40-70: 1000: 5-20: 5000-10000, lithium sulfonate is added to the organic solvent and dispersed evenly, and then carbon nanotube-doped porous graphite and lithium supplement are added and dispersed evenly, and spray drying (inlet temperature 180°C, outlet temperature 80°C, flow rate 0.1kg / h, 1h) is performed to obtain a graphite composite material.

[0013] The method for preparing porous graphite in step S1 is as follows: 100 parts of artificial graphite, (10-30) parts of pore-forming agent, and (5-15) parts of sulfur-based cross-linking agent are mixed evenly, then heated to 500-800° C. for carbonization for 1-6 hours, and then heated to 2800-3200° C. for graphitization for 6-24 hours to obtain porous graphite.

[0014] The sulfur-based crosslinking agent is one of ammonium polysulfide, thioglycolic acid, 2-mercaptobenzoic acid or ethyl 2-mercaptopropionate; the pore-forming agent is one of polyvinyl alcohol, methyl methacrylate, polyvinyl chloride or polystyrene.

[0015] In step S1, the catalyst is one of chlorides and nitrates of iron, cobalt and nickel; the organic polymer is one of dopamine, aniline and pyrrole; the oxidant is one of persulfate, perchlorate, periodate or hydrogen peroxide; and the anhydride crosslinking agent is one of maleic anhydride, citraconic anhydride, phenyl maleic anhydride, 2,3-diphenyl maleic anhydride or dimethyl maleic anhydride.

[0016] In step S2, the carbon source gas is one of methane, ethane, ethylene, acetylene and propyne.

[0017] In step S3, the lithium supplement agent is one of Li5FeO4, Li2NiO2, Li6CoO4, and Li4V3O8; the organic solvent is one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, ethyl acetate, methyl acetate, and ethyl propionate.

[0018] The lithium sulfonate in step S3 is one of lithium trifluoromethanesulfonate, lithium dinonylnaphthalenesulfonate, lithium 4-methylbenzenesulfonate, lithium perfluorohexanesulfonate, and lithium perfluorobutylsulfonate.

[0019] A fast-charging, low-temperature graphite composite material is used in lithium-ion batteries.

[0020] Beneficial effects:

[0021] 1. Add catalyst, organic polymer, oxidant and anhydride crosslinking agent into porous graphite, use the crosslinking agent to form a porous structure, and at the same time, the organic polymer is carbonized and decomposed to generate a porous carbon structure with high isotropy and low expansion. At the same time, the porous graphite is doped with a catalyst and used as a matrix to grow carbon nanotubes in a carbon source atmosphere to improve the electronic conductivity of the porous core.

[0022] 2. The spray drying method is used to coat lithium sulfonate and lithium replenisher on the surface of carbon nanotube-doped porous graphite, and the high solvation ability between lithium sulfonate and electrolyte solvent is used to improve the lithium ion insertion and extraction rate. At the same time, the lithium replenisher releases lithium ions during the charging and discharging process, reducing the lithium ions consumed in forming the SE I film and improving the initial efficiency. At the same time, the released lithium ions improve fast charging and low-temperature performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the SEM image of the graphite composite material prepared in Example 1. DETAILED DESCRIPTION

[0024] Example 1

[0025] The preparation method of porous graphite is:

[0026] 100 g of artificial graphite, 20 g of polyvinyl alcohol, and 10 g of ammonium polysulfide were mixed evenly, then heated to 650° C. for carbonization for 3 h, and then heated to 3000° C. for graphitization for 12 h to obtain porous graphite.

[0027] A method for preparing a fast-charging low-temperature graphite composite material comprises the following steps:

[0028] Step S1:

[0029] 20 g of dopamine was dissolved in 400 g of N-methylpyrrolidone to prepare a 5 wt% solution, and then 3 g of ferric chloride, 3 g of maleic anhydride, and 100 g of porous graphite were added and dispersed evenly, and then 10 g of ammonium persulfate was added dropwise and dispersed evenly, and reacted at a temperature of 4° C. for 3 h, filtered, and the obtained filter residue was carbonized at 1200° C. for 6 h to obtain catalyst-doped porous graphite;

[0030] Step S2:

[0031] The catalyst-doped porous graphite was transferred to a tube furnace, and then the temperature was raised to 900°C and ethylene gas was introduced at a flow rate of 300 SCCM for 120 minutes to obtain carbon nanotube-doped porous graphite by vapor deposition method;

[0032] Step S3:

[0033] 50g of lithium trifluoromethanesulfonate was added to 7500g of ethylene carbonate and dispersed evenly, then 1000g of carbon nanotube-doped porous graphite and 10g of Li5FeO4 were added and dispersed evenly, and spray dried (inlet temperature 180°C, outlet temperature 80°C, flow rate 0.1kg / h, 1h) to obtain a graphite composite material.

[0034] Example 2

[0035] Preparation method of porous graphite:

[0036] 100g of artificial graphite, 10g of methyl methacrylate and 5g of thioglycolic acid were mixed evenly, then heated to 500°C for carbonization for 6h, and then heated to 2800°C for graphitization for 24h to obtain porous graphite.

[0037] A method for preparing a fast-charging low-temperature graphite composite material comprises the following steps:

[0038] Step S1:

[0039] 10g of aniline was dissolved in 1000g of N-methylpyrrolidone to prepare a 1wt% solution, and then 1g of nickel chloride, 1g of citraconic anhydride and 100g of porous graphite were added and dispersed evenly, and then 5g of sodium perchlorate was added dropwise and dispersed evenly, and reacted at a temperature of 0°C for 6h, filtered, and the obtained filter residue was carbonized at 1000°C for 12h to obtain catalyst-doped porous graphite;

[0040] Step S2:

[0041] The catalyst-doped porous graphite was transferred to a tube furnace, and then the temperature was raised to 800°C and acetylene gas was introduced at a flow rate of 100 SCCM for 300 minutes to obtain carbon nanotube-doped porous graphite by vapor deposition method;

[0042] Step S3:

[0043] 40 g of lithium dinonylnaphthalenesulfonate was added to 5000 g of propylene carbonate and dispersed evenly, and then 1000 g of carbon nanotube-doped porous graphite and 5 g of Li2NiO2 were added and dispersed evenly, and spray-dried (inlet temperature 180°C, outlet temperature 80°C, flow rate 0.1 kg / h, 1 h) to obtain a graphite composite material.

[0044] Example 3

[0045] Preparation method of porous graphite:

[0046] 100 g of artificial graphite, 30 g of polyvinyl chloride, and 15 g of 2-mercaptobenzoic acid were mixed evenly, then heated to 800° C. for carbonization for 1 h, and then heated to 3200° C. for graphitization for 6 h to obtain porous graphite.

[0047] A method for preparing a fast-charging low-temperature graphite composite material comprises the following steps:

[0048] Step S1:

[0049] 10g of pyrrole was dissolved in 100g of N-methylpyrrolidone to prepare a 10wt% solution, and then 5g of cobalt chloride, 5g of phenyl maleic anhydride and 100g of porous graphite were added and dispersed evenly, and then 20g of hydrogen peroxide oxidant was added dropwise and dispersed evenly, and reacted at a temperature of 15°C for 1h, filtered, and the obtained filter residue was carbonized at 1400°C for 2h to obtain catalyst-doped porous graphite;

[0050] Step S2:

[0051] The catalyst-doped porous graphite was transferred to a tube furnace, and then the temperature was raised to 1000°C and methane gas was introduced at a flow rate of 500 SCCM for 30 minutes to obtain carbon nanotube-doped porous graphite.

[0052] Step S3:

[0053] 70g of lithium 4-methylbenzenesulfonate was added to 10000g of dimethyl carbonate and dispersed evenly, then 1000g of carbon nanotube-doped porous graphite and 20g of Li6CoO4 were added and dispersed evenly, and spray dried (inlet temperature 180°C, outlet temperature 80°C, flow rate 0.1kg / h, 1h) to obtain a graphite composite material.

[0054] Comparative Example 1:

[0055] The difference from Example 1 is that the outer layer is not coated with Li5FeO4 lithium supplement agent, and the rest is the same as Example 1.

[0056] Comparative Example 2:

[0057] The difference from Example 1 is that the outer layer is not coated with lithium trifluoromethanesulfonate, and the rest is the same as Example 1.

[0058] 1. SEM test

[0059] The graphite composite material obtained in Example 1 was subjected to SEM testing, and the results are as follows: Figure 1 As shown in the figure, it can be seen that the graphite composite material prepared in Example 1 presents a secondary granular structure with uniform size distribution and a particle size between 10-15 μm.

[0060] 2. Physical and chemical properties and button battery test

[0061] The graphite composite materials prepared in Examples 1-3 and Comparative Examples 1-2 were tested for specific surface area, powder OI value, specific capacity, and initial efficiency. Test method: GBT-24533-2019 "Graphite negative electrode materials for lithium-ion batteries". At the same time, the powder resistivity of the material was tested by a four-probe tester.

[0062] The graphite composite materials obtained in Examples 1-3 and Comparative Examples 1-2 are respectively assembled into button batteries A1, A2, A3, B1, and B2; the preparation method thereof is as follows: a binder, a conductive agent, and a solvent are added to the negative electrode material, stirred to make a slurry, coated on a copper foil, and dried and rolled to obtain the battery. The binder used is LA132 binder, the conductive agent is SP, the negative electrode material is the graphite composite material prepared in Examples 1-3 and Comparative Examples 1-2, the solvent is double distilled water, and the ratio is: negative electrode material: SP: LA132: double distilled water = 94g: 2g: 4g: 220mL, and a negative electrode plate is prepared; the electrolyte is LiPF6 / EC+DEC (volume ratio 1:1, concentration 1.1mol / L), the metal lithium sheet is the counter electrode, the diaphragm is a polyethylene PE film, the simulated battery assembly is carried out in an argon-filled glove box, and the electrochemical performance is carried out on a Wuhan Blue Electric CT2001A battery tester, the charge and discharge voltage range is 0.005V-2.0V, and the charge and discharge rate is 0.1C. At the same time, the charging DCR (50% SOC) of the button battery is tested, and the diffusion coefficient of the materials of Examples 1-3 and Comparative Examples 1-2 is tested by GITT, and the test results are as shown in Table 1:

[0063] Table 1

[0064]

[0065]

[0066] As can be seen from Table 1, compared with Comparative Examples 1-2, the first discharge capacity and first efficiency, rate performance and cycle performance of the graphite composite materials prepared in Examples 1-3 are significantly improved. The reason is that lithium sulfonate is coated on the surface of the graphite shell to reduce its irreversible capacity and improve the diffusion coefficient of lithium ions during the charge and discharge process, thereby improving the first efficiency and reducing the DCR; at the same time, the core is doped with carbon nanotubes to reduce the powder resistance of the material and reduce the DCR.

[0067] 3. Soft pack battery test:

[0068] The graphite composite materials prepared in Examples 1-3 and Comparative Examples 1-2 were used as negative electrodes, and the ternary material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 The positive electrode was prepared by using Li PF6 (the solvent was EC+DEC, the volume ratio was 1:1, the concentration was 1.1 mol / L) as the electrolyte and cel egard 2400 as the separator to prepare a 2Ah soft-pack battery.

[0069] 3.1 Rate performance test

[0070] The charge and discharge voltage range is 2.8~4.2V, the test temperature is 25±3.0℃, and the constant current ratio is tested at 1.0C, 2.0C, 3.0C, and 5.0C respectively, and the discharge is tested at 1.0C. The results are shown in Table 2:

[0071] Table 2

[0072] Examples magnification 1C 2C 3C 5C Example 1 Constant current ratio (%) 97.72 95.78 93.44 87.58 Example 2 Constant current ratio (%) 96.71 95.15 92.77 86.28 Example 3 Constant current ratio (%) 98.25 96.46 94.36 88.26 Comparative Example 1 Constant current ratio (%) 95.46 92.34 88.47 81.82 Comparative Example 2 Constant current ratio (%) 94.51 91.23 87.37 80.72

[0073] As can be seen from Table 2, the rate charging performance of the soft-pack battery in the embodiment of the present invention is significantly better than that in the comparative example, that is, the charging time is shorter, indicating that the composite negative electrode material of the present invention has good fast charging performance. The reason may be that the embodiment material has a lower OI value and its high diffusion coefficient improves the kinetic performance of the material.

[0074] 3.2 Low temperature performance

[0075] The batteries of the embodiment and the comparative example were tested for discharge capacity W1 at a rate of 0.33C at room temperature. They were then placed at -20°C and tested for discharge capacity W2 at a rate of 0.1C. The low temperature capacity retention rate = W2 / W1 was then calculated and the results are shown in Table 3.

[0076] Table 3

[0077] Examples Low temperature capacity retention rate Example 1 87.9% Example 2 85.6% Example 3 89.3% Comparative Example 1 80.1% Comparative Example 2 81.7%

[0078] It can be seen from Table 3 that the low-temperature capacity retention rate of the lithium-ion battery prepared with the graphite composite negative electrode material prepared in the present invention is significantly better than that of the comparative example. The reason is that the surface of the example material is coated with lithium sulfonate and its lithium supplement, which improves the diffusion coefficient under low temperature conditions and improves the low-temperature capacity retention rate.

[0079] Although the preferred embodiments of the present invention have been described above in conjunction with the accompanying drawings, they are not intended to limit the scope of protection of the present invention. For those skilled in the art, the present invention may have various modifications and variations, and any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A fast-charging low-temperature graphite composite material, characterized in that: The composite material presents a core-shell structure, the core is porous graphite and its doped carbon nanotubes, and the shell is composed of a lithium supplement and its lithium sulfonate complex; calculated based on the composite material mass ratio of 100%, the shell accounts for 2-8wt%.

2. The fast-charging low-temperature graphite composite material according to claim 1, characterized in that: The shell is composed of 5-20wt% lithium supplement agent, 40-70wt% lithium sulfonate and the rest is lithium binder.

3. The method for preparing a fast-charging low-temperature graphite composite material according to claim 1, characterized in that: The steps include: Step S1: According to the mass ratio of porous graphite: catalyst: organic polymer: oxidant: anhydride cross-linking agent = 100: 1-5: 10-30: 5-20: 1-5, the organic polymer is dissolved in an organic solvent to prepare a 1-10wt% solution, then the catalyst, anhydride cross-linking agent, and porous graphite are added and dispersed evenly, then the oxidant is added dropwise and dispersed evenly, and the mixture is reacted at a temperature of 0-15°C for 1-6h, filtered, and the obtained filter residue is carbonized at 1000-1400°C for 2-12h to obtain catalyst-doped porous graphite; Step S2: The catalyst-doped porous graphite is transferred to a tube furnace, and then the temperature is raised to 800-1000° C. by a vapor deposition method, and a carbon source gas is introduced at a flow rate of 100-500 SCCM for 30-300 minutes to obtain carbon nanotube-doped porous graphite; Step S3: According to the mass ratio of lithium sulfonate: carbon nanotube-doped porous graphite: lithium supplement: organic solvent = 40-70: 1000: 5-20: 5000-10000, lithium sulfonate is added to the organic solvent and dispersed evenly, and then carbon nanotube-doped porous graphite and lithium supplement are added and dispersed evenly, and spray drying (inlet temperature 180°C, outlet temperature 80°C, flow rate 0.1kg / h, 1h) is performed to obtain a graphite composite material.

4. The method for preparing a fast-charging low-temperature graphite composite material according to claim 3, characterized in that: The method for preparing porous graphite in step S1 is as follows: 100 parts of artificial graphite, (10-30) parts of pore-forming agent, and (5-15) parts of sulfur-based cross-linking agent are mixed evenly, then heated to 500-800° C. for carbonization for 1-6 hours, and then heated to 2800-3200° C. for graphitization for 6-24 hours to obtain porous graphite.

5. The method for preparing a fast-charging low-temperature graphite composite material according to claim 4, characterized in that: The sulfur-based crosslinking agent is one of ammonium polysulfide, thioglycolic acid, 2-mercaptobenzoic acid or ethyl 2-mercaptopropionate; the pore-forming agent is one of polyvinyl alcohol, methyl methacrylate, polyvinyl chloride or polystyrene.

6. The method for preparing a fast-charging low-temperature graphite composite material according to claim 3, characterized in that: In step S1, the catalyst is one of chlorides or nitrates of iron, cobalt, and nickel; the organic polymer is one of dopamine, aniline, and pyrrole; the oxidant is one of persulfate, perchlorate, periodate, or hydrogen peroxide; and the anhydride crosslinking agent is one of maleic anhydride, citraconic anhydride, phenyl maleic anhydride, 2,3-diphenyl maleic anhydride, or dimethyl maleic anhydride.

7. The method for preparing a fast-charging low-temperature graphite composite material according to claim 3, characterized in that: In step S2, the carbon source gas is one of methane, ethane, ethylene, acetylene and propyne.

8. The method for preparing a fast-charging low-temperature graphite composite material according to claim 3, characterized in that: In step S3, the lithium supplement agent is one of Li5FeO4, Li2NiO2, Li6CoO4, and Li4V3O8; the organic solvent is one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, ethyl acetate, methyl acetate, and ethyl propionate.

9. The method for preparing a fast-charging low-temperature graphite composite material according to claim 3, characterized in that: The lithium sulfonate in step S3 is one of lithium trifluoromethanesulfonate, lithium dinonylnaphthalenesulfonate, lithium 4-methylbenzenesulfonate, lithium perfluorohexanesulfonate, and lithium perfluorobutylsulfonate.

10. A fast-charging, low-temperature graphite composite material according to claims 1-9 is applied to lithium-ion batteries.

Citation Information

Patent Citations

  • Porous lithium salt aerogel coated graphite composite material and preparation method thereof

    CN109904434A

Cited By

  • Fast ion conductor composite material and preparation method thereof, secondary battery and electric device

    CN119852381A

  • A fast ion conductor composite material, a preparation method thereof, a secondary battery, and an electrical device

    CN119852381B